North America's Indian Trade in European Commerce and Imagination, 1580-1850 - Colpitts, George (Early American history series., 2013)
In North America's Indian Trade in European Commerce and Imagination, Colpitts analyzes the imaginative and intellectual response of Europeans to their expanding trade relations with America's people in the period of colonization.